Secure Communication for Integrated Satellite-Terrestrial Backhaul Networks: Focus on Up-Link Secrecy Capacity Based on Artificial Noise - Liu, Shanyun; Zhu, Xiangming; Chen, Hongyang; Han, Zhu (IEEE wireless communications letters, 2023)
This letter focuses on the secure communications in integrated satellite-terrestrial backhaul networks (ISTBNs), where the base stations are capable of processing legitimate signals and transmitting the jamming signal to interfere with eavesdroppers. To this end, we exploit artificial noise (AN) to improve the up-link secrecy capacity subject to communication resource constraints. Also, the condition for the existence of secure communication is given in this letter. Under this condition, the optimal transmit power and the AN interference power are derived to maximize the up-link secrecy capacity. Numerical results demonstrate that the proposed AN-based transmission framework can guarantee the secure transmission performance in ISTBNs under the existence of malicious eavesdroppers.